Evaluation of solar dryer/air heater performance and the accuracy of the result - Srivastava A.K.; Shukla S.K.; Mishra S. (My University, 2025)
This paper investigates the feasibility of using Lauric acid as a phase change material (PCM) to store excess solar energy and release it when the energy availability is inadequate or not available for solar drying process. With the increased emphasis on the efficiency of solar heating and drying facilities, the performance of ancillary equipment is becoming increasingly important. The air heater is a source of lost thermal efficiency in two ways - Air leakage into dryer side and poor heat recovery. Moreover, air in leak makes it difficult to determine the exiting hot air temperature and the performance of the air heater. In the present study, attention was given on the heat transfer characteristics of the PCM during the charge and discharge periods. The effects of inlet hot air temperature and inlet air velocities on the charge time were determined, while during the discharge period only the effect of inlet ambient air velocity was considered. This study also addresses the issue of properly evaluating the air heater performance and the accuracy of the final result. The appendix discusses the procedures used to determine the individual measurements and the uncertainty of these measurements. © 2014 The Authors Published by Elsevier Ltd.